Design of MIDI decoder for auto angklung - Anis Hazwana, Mohamad Wazir (2013)
This project describes' a controller device, called MIDI (Music Instrument Digital interface) to control an Angklung (Traditional Music Instrument) with 2 Octaves diatonic automatically. MIDI device or MID! files will generate MID! data which is decoded into music synthesis commands to the electric motor (DC Motor). Angklung will be control from MIDI Keyboard or Computer as interface. This project will show how far the accuracy of the way to play Angklungs between human and autonomous technology.